Knowledge discovery process supporting organizational learning - Ramos, Isabel (2003)
This paper stresses the contribution of the process of knowledge discovery in databases for the effective creation and sharing of organizational knowledge. The focus on the process of knowledge discovery has been mainly technological. The paper attempts to enrich that perspective by stressing the insights gained by integrating the knowledge discovery process in the social process of knowledge construction that makes the knowledge discovery process meaningful. A test case is presented, in which a component of the Portuguese Army Database was explored with the PADRÃO system. This system, for knowledge discovery in geo-referenced databases, integrates a set of databases and principles of qualitative spatial reasoning. The PADRÃO approach and the obtained results are then discussed in order to stress the insights that emerge when the focus change from technology to social construction of knowledge.